2021
DOI: 10.1002/jcla.24078
|View full text |Cite
|
Sign up to set email alerts
|

miR‐125a‐5p promotes gastric cancer growth and invasion by regulating the Hippo pathway

Abstract: This is an open access article under the terms of the Creat ive Commo ns Attri bution-NonCo mmercial License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited and is not used for commercial purposes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 44 publications
0
9
0
Order By: Relevance
“…It has been confirmed that miR-125a-5p facilitates osteoclastogenesis via targeting TNFRSF1B ( 19 ). In gastric cancer, miR-125a-5p was found to promote gastric cancer cell growth and invasion by activating the Hippo pathway ( 20 ). We conducted the correlation analysis, expression analysis, and prognosis analysis.…”
Section: Discussionmentioning
confidence: 99%
“…It has been confirmed that miR-125a-5p facilitates osteoclastogenesis via targeting TNFRSF1B ( 19 ). In gastric cancer, miR-125a-5p was found to promote gastric cancer cell growth and invasion by activating the Hippo pathway ( 20 ). We conducted the correlation analysis, expression analysis, and prognosis analysis.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that herpes simplex virus 1 infection can cause gastric cancer, and the Hippo signaling pathway is closely related to the in ltration and metastasis of gastric cancer. FBXW5 and miR-125a-5p promote the deterioration of gastric cancer cells by inactivating the Hippo signaling pathway [18][19][20][21]. People who are susceptible to H. pylori have a high probability of suffering from gastric cancer.…”
Section: Discussionmentioning
confidence: 99%
“…According to the Global Cancer Statistics 2020 report, the number of new cancer cases is 19.29 million, the number of new deaths is expected to be 9.95 million and 28.4 million new cancer cases are expected in 2040, an increase of 47% from 2020, with gastric cancer ranking fth in global cancer incidence and fourth in cause of death [1]. The common treatments for gastric cancer include surgical resection and chemotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…This miRNA from S. japonicum presents an identical seed sequence (2–8 nt in the 5′ region) to that of the human miRNA Hsa-miR-125a-5p. Interestingly, Hsa-miR-125a-5p may function as a powerful tumor promoter [ 121 ]. Thus, the miRNAs of helminths can share sequence similarities with human miRNAs and could show a similar capacity regarding the promotion or inhibition of tumor development.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…Other mechanisms regulating gene expression, the availability of molecular targets, and the cellular context must be considered. For example, Hsa-miR-125a-5p can present oncogenic activity or tumor-suppressor functions in different types of cancer [ 121 ].…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%